The Paradox of Agrarian Reform on Ex-HGU/PTPN Land: Between Land Rights and Criminalization - Asep Sapsudin (UIN Sunan Gunung Djati Bandung, 2026)
This study highlights tenure conflicts occurring in the Pangalengan coffee plantation area, Bandung Regency, focusing on the ambiguous status of land formerly under HGU (Land Use Rights) or currently managed by PTPN VIII, which has become a source of competing claims and potential socio-agrarian conflicts. Through a socio-legal approach and an analysis of legal pluralism, this study reveals the gap between the top-down normative discourse on agrarian reform and the repressive criminal law practices on the ground. Local farming communities, with limited access to capital, have established informal legal claims based on the history of land cultivation, the productive use of coffee plants, the principle of the social function of land as stipulated in the 1960 Land Law (UUPA), and the hope for land redistribution through the Presidential Regulation on Agrarian Reform. On the other hand, state-owned corporations and law enforcement agencies enforce a formal, positivist-legalistic legal framework to protect assets through legal notices and criminalization under Article 385 of the Criminal Code (KUHP) or sector-specific criminal regulations for plantations. Field data and in-depth interviews reveal an agrarian paradox: the land redistribution program through TORA is hampered by convoluted and sluggish bureaucracy, while the enforcement of criminal law by corporations proceeds swiftly, undermining the solidarity of grassroots movements. The arrests of farmers’ union activists not only cause psychological trauma, poverty, and damage to sustainable communal agricultural systems, but also reinforce the large-scale land monopoly held by a small elite across generations. The state must shift away from a normative security approach and redefine agrarian reform as a model for a more equitable distribution of the benefits of natural resources in order to prevent the escalation of ecological and social crises in the future.